2020
DOI: 10.1038/s41467-020-16662-2
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GCN2/ATF4 signals in amygdalar PKC-δ neurons promotes WAT browning under leucine deprivation

Abstract: The browning of white adipose tissue (WAT) has got much attention for its potential beneficial effects on metabolic disorders, however, the nutritional factors and neuronal signals involved remain largely unknown. We sought to investigate whether WAT browning is stimulated by leucine deprivation, and whether the amino acid sensor, general control nonderepressible 2 (GCN2), in amygdalar protein kinase C-δ (PKC-δ) neurons contributes to this regulation. Our results show that leucine deficiency can induce WAT bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…Similarly, we found that Ucp1 expression was increased in mice and rats fed with a valine‐deficient diet, and Guo and colleagues showed that both valine and isoleucine deficiency increase lipid mobilization and energy expenditure suggesting that hypermetabolism is a conserved response to amino acid imbalance 68,85 . Other investigators demonstrated that leucine deprivation induced the induction of Ucp1 and other markers of thermogenic activation (generally known as ‘browning’) in WAT, via a CNS pathway and activation of sympathetic outflow 92 . The evolutionary benefit of this increase in metabolic rate and metabolic reprogramming of adipose tissue in an undernourished animal is not immediately clear, but may be important to balance the energy demands of foraging, via SNS‐mediated activation of lipolysis 90 …”
Section: Protein Malnutritionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, we found that Ucp1 expression was increased in mice and rats fed with a valine‐deficient diet, and Guo and colleagues showed that both valine and isoleucine deficiency increase lipid mobilization and energy expenditure suggesting that hypermetabolism is a conserved response to amino acid imbalance 68,85 . Other investigators demonstrated that leucine deprivation induced the induction of Ucp1 and other markers of thermogenic activation (generally known as ‘browning’) in WAT, via a CNS pathway and activation of sympathetic outflow 92 . The evolutionary benefit of this increase in metabolic rate and metabolic reprogramming of adipose tissue in an undernourished animal is not immediately clear, but may be important to balance the energy demands of foraging, via SNS‐mediated activation of lipolysis 90 …”
Section: Protein Malnutritionsupporting
confidence: 68%
“…68,85 Other investigators demonstrated that leucine deprivation induced the induction of Ucp1 and other markers of thermogenic activation (generally known as 'browning') in WAT, via a CNS pathway and activation of sympathetic outflow. 92 The evolutionary benefit of this increase in metabolic rate and metabolic reprogramming of adipose tissue in an undernourished animal is not immediately clear, but may be important to balance the energy demands of foraging, via SNS-mediated activation of lipolysis. 90…”
Section: Resting Metabolic Ratementioning
confidence: 99%
“…21 GCN2 activation in amygdalar PKC-δ neurons facilitates WAT browning under leucine deprivation. 14 These findings suggest that macrophage GCN2 may play a role in leucine deprivation-induced other metabolic effects, such as WAT browning and lipolysis. In this study, we aimed to investigate whether ATMs are involved in leucine deprivation-induced WAT browning and lipolysis and whether GCN2 in ATMs contribute to this regulation.…”
Section: Introductionmentioning
confidence: 90%
“…The sections were subjected to hematoxylin and eosin (H&E) staining after deparaffinization and rehydration. 14 For UCP1 immunohistochemistry (IHC), the WAT sections were subjected to antigen retrieval in citrate acid buffer (pH 6.0) at 95°C for 20 minutes after deparaffinization and rehydration. After blocking with 5% goat serum in 0.1 M phosphate buffer and 0.2% Triton X-100 for 1 hour at room temperature, the WAT sections were incubated overnight at 4°C with anti-UCP1 antibody (1:500; ab10983, Abcam, Cambridge, UK) 22 and then incubated with HRP-conjugated secondary antibodies (1:1000; Jackson ImmunoResearch, PA, USA).…”
Section: Histopathology and Ucp1 Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation